Penyusunan dan Pelaksanaan Desain Evaluasi Formatif di SD Negeri Paninggilan 06 Ciledug Kota Tangerang - Pratiwi, Desti; Rossy, Rossy; Aprilya, Anggi (TSAQOFAH, 2022)
Learning evaluation is an activity of collecting data and information. Regarding students' learning abilities to assess the degree of lesson plans. Always running, it can also be used as a tool to assess. The purpose of this study was to identify formative evaluation as applied in elementary schools. This research method is qualitative with a case study design. The population used by the researchers were students and teachers of SD Negeri Paninggilan 6. Based on the results of the study and also the discussion of this research, namely learning design in the realm of assessment or formative evaluation which was applied after the teacher carried out the process of delivering material, the basic factor was in the form of learning methods that became a way for teachers. convey learning, and of course in accordance with the learning objectives, then there are assumptions that must be applied in conducting formative evaluations both long and short term, not forgetting the source that refers to teachers carrying out learning namely lesson plans and formative assessment itself which is the main thing in seeing the development and ability of students in learning.